Systematic Literature Review: The Effect of Giving Rewards on Students' Learning Motivation in Islamic Religious Education Lessons - Salsabina S, Laila (Aksara Shofa, 2023)
This study aims to determine the effect of giving rewards on students' learning motivation in Islamic Religious Education subjects at SMP IT ArRudho, East Jakarta City. In this study, using the field research method, namely field research or observation and the distribution of instruments in the form of a questionnaire that will be collected and used as a source for analysis. Hypothesis testing using Pearson product moment correlation is to find a correlation or relationship between variable X (Giving Reward) with variable Y (Learning Motivation). The results of this study indicate that there is an effect of giving rewards on students' learning motivation, this can be seen from the value of the correlation index (rcount) which is 0.401 (r table) 0.254, meaning that there is a fairly strong influence of giving rewards on students' learning motivation. So it can be concluded that the provision of rewards can increase student learning motivation. So that the provision of rewards can encourage students to be more active in the learning process at school.